S-nitrosylation of EZH2 alters PRC2 assembly, methyltransferase activity, and EZH2 stability to maintain endothelial homeostasis - Ashima Sakhuja; Ritobrata Bhattacharyya; Yash Tushar Katakia; Shyam Kumar Ramakrishnan; Srinjoy Chakraborty; Hariharan Jayakumar; Shailesh Mani Tripathi; Niyati Pandya Thakkar; Sumukh Thakar; Sandeep Sundriyal; Shibasish Chowdhury; Syamantak Majumder (Nature Communications)
Abstract Nitric oxide (NO), a versatile bio-active molecule modulates cellular functions through diverse mechanisms including S-nitrosylation of proteins. Herein, we report S-nitrosylation of selected cysteine residues of EZH2 in endothelial cells, which interplays with its stability and functions. We detect a significant reduction in H3K27me3 upon S-nitrosylation of EZH2 as contributed by the early dissociation of SUZ12 from the PRC2. Moreover, S-nitrosylation of EZH2 causes its cytosolic translocation, ubiquitination, and degradation. Further analysis reveal S-nitrosylation of cysteine 329 induces EZH2 instability, whereas S-nitrosylation of cysteine 700 abrogates its catalytic activity. We further show that S-nitrosylation-dependent regulation of EZH2 maintains endothelial homeostasis in both physiological and pathological settings. Molecular dynamics simulation reveals the inability of SUZ12 to efficiently bind to the SAL domain of EZH2 upon S-nitrosylation. Taken together, our study reports S-nitrosylation-dependent regulation of EZH2 and its associated PRC2 complex, thereby influencing the epigenetics of endothelial homeostasis.